NiO–ZnO Nanoheterojunction Networks for Room‐Temperature Volatile Organic Compounds Sensing. Issue 22 (12th September 2018) - Chen, Hongjun; Bo, Renheng; Shrestha, Aabhash; Xin, Bobo; Nasiri, Noushin; Zhou, Jin; Di Bernardo, Iolanda; Dodd, Aaron; Saunders, Martin; Lipton‐Duffin, Josh; White, Thomas; Tsuzuki, Takuya; et al.
Abstract: Engineering of highly performing nanomaterials, capable of rapid detection of trace concentrations of gas molecules at room temperature, is key to the development of the next generation of miniaturized chemical sensors. Here, a highly performing nanoheterojunctions layout is presented for the rapid room‐temperature chemical sensing of volatile organic compounds down to ten particles per billion concentrations. The layout consists of a 3D network of nickel oxide–zinc oxide (NiO–ZnO) p–n semiconductors with grain size of ≈20 nm nanometers and a porosity of ≈98%. Notably, it is observed that the formation of the p–n heterojunctions by decoration of a ZnO nanoparticle networks with NiO increases the sensor response by more than four times while improving the lower limit of detection. Under solar light irradiation, the optimal NiO–ZnO nanoheterojunction networks demonstrate a strong and selective room‐temperature response to two important volatile organic compounds utilized for breath analysis, namely acetone and ethanol. Furthermore, these NiO–ZnO nanoheterojunctions show an inverse response to acetone from that observed for all others reducing gas molecules (i.e., ethanol, propane, and ethylbenzene). It is believed that these novel insights of the optoelectrochemical properties of ultraporous nanoheterojunction networks provide guidelines for the future design of low‐power solid‐state chemical sensors. Abstract : 3D ultraporous network of NiO–ZnO is constructed for the detection of volatile organic compounds at room temperature under solar irradiation. The formation of p–n nanoheterojunctions not only increases the sensor response, but also improves the lower limit of detection, which provides guideline for the design of low‐power solid‐state chemical sensors in the near future.